DEVELOPMENT OF CREATIVE ACTIVITY OF ELEMENTARY SCHOOL STUDENTS AS A PEDAGOGICAL PROBLEM (World Bulletin of Social Sciences, 2024)
This article is about today's primary school teacher's knowledge of what abilities their students have, their desire to learn, the level of mastery of the learning material, their recall and their knowledge. The issue of the actual task of today, based on the extent to which the student can use it to perform tasks, think carefully when solving problems, and master verbal and non-verbal speech, is widely covered.